The Impact of GRDP, Capital Expenditure, Investment, Education, and Wage on Unemployment in West Java - Soekotjo, Nazwa Putri; Susilo (Journal of Development Economic and Social Studies, 2026)
Unemployment remains a crucial issue in the Indonesian economy, especially in West Java, which consistently records the highest unemployment rate in Indonesia. This research aims to obtain the effect of Gross Regional Domestic Product (GRDP), capital expenditures, Domestic Investment, education, and minimum wage on the unemployment rate in West Java from 2019-2024. Using a quantitative approach with panel data regression, the results of this research shown that GRDP, Domestic Investment, and education have a significant and negative effects on the unemployment rate, while minimum wage has a significant and positive effects on the employment rate. On the other side, capital expenditure and do not effect on the unemployment rate. Simultaneously, GRDP, capital expenditure, Domestic Investment, education, and minimum wage have a significant effect with a coefficient of determination of 88,8%.